Implications of the Precise Anatomical Location of Lumbar Stenosis for Minimally Invasive Decompressive Lumbar Surgery - Donald A. Ross; Mehtab Sal; Jasper Erickson; Maxwell Cretcher; Ningcheng (Peter) Li; Jeffery M. Pollock (Journal of Minimally Invasive Spine Surgery and Technique, 2021)
Objective The purpose of this study was to characterize an observation that the most severe lumbar stenosis is often displaced from the disc. Methods A retrospective magnetic resonance (MRI) review of displacement and causes of lumbar canal stenosis, was undertaken. Lumbar MRIs (n=3000) were reviewed for stenosis defined as a canal diameter of ≤8 mm. Displacement of maximal stenosis from the disc was measured; measurements inferior to the disc were assigned negative values. Defined causes were; ligamentous hypertrophy, facet hypertrophy, lipomatosis, spondylolisthesis, synovial cyst, or adjacent segment disease. Results Lumbar stenosis levels (n=1,042) identified in 749 patients were; L1-2 (3.8%), L2-3(20.1%), L3-4 (35.3%), L4-5 (37.7%), and L5-S1 (3.2%). Of these levels 20.8% were attributed to facet hypertrophy, 29.8% ligamentous hypertrophy, 31.1% epidural lipomatosis, 11.2% spondylolisthesis, 5.6% adjacent segment disease, and 1.5% synovial cyst. Mean displacement stenosis (mm) was; synovial cyst (-0.3; range 7 to -5), epidural lipomatosis, (-1.1; 5 to -13), ligamentous hypertrophy (-3.5; 5 to -13); facet hypertrophy (-3.9; 7 to -11), adjacent segment disease (-4.7; 7 to -11), and spondylolisthesis (-4.9; 11 to -12). Sub-group analysis revealed a predominantly negative displacement for spondylolisthesis, adjacent segment disease, facet hypertrophy, and ligamentous hypertrophy. Conclusion The site of maximal lumbar stenosis is at or near the center of the disc with lipomatosis or synovial cyst, but significantly inferiorly displaced when ligamentous or facet hypertrophy, spondylolisthesis, or adjacent segment disease is the major cause. Lipomatosis as a cause of stenosis is more common than previously reported.